Analysis of the Transformational Leadership Style of the Principal and the Factors Influencing Teacher Performance at SD Inpres Dagimon, Mappi Regency, South Papua Province - Bria, Maria Anselmia; Wahyuningsih, Sri; Rohayati, Yeti (Majapahit Journal of Islamic Finance and Management, 2025)
This study is motivated by the educational challenges in disadvantaged, frontier, and outermost (3T) regions, particularly Mappi Regency, South Papua, where limited infrastructure, low teacher discipline, and weak supervision demand transformational leadership from school principals to enhance teacher performance. The study aims to analyze the transformational leadership style of the school principal and its influence on teacher performance at SD Inpres Dagimon. A qualitative approach with a single case study design was employed. Data were collected through in-depth interviews, participatory observation, and document analysis, with validation conducted via source triangulation. The findings reveal that teachers’ perceptions of transformational leadership encompass four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Such leadership positively impacts work motivation, discipline, instructional innovation, and teacher collaboration. The implication is that the application of transformational leadership constitutes a key strategy in addressing educational challenges in 3T regions and in enhancing sustainable learning quality.